New fast turn-on speed SCR device for electrostatic discharge protection. (November 2016) - Liao, Changjun; Liu, Jizhi; Liu, Zhiwei
Abstract: A new SCR with the variation lateral base doping (VLBD) structure (VSCR) is proposed to improve the turn-on speed for electrostatic discharge (ESD) protection. The turn-on speed of the SCR was determined mainly by the base transit time of the parasitic p-n-p and n-p-n transistors of the SCR, and the VLBD structure can reduce the base transit time of the bipolar transistors to improve the turn-on speed of the SCR. The experimental and simulation results show that the turn-on time of the VSCRs with the VLBD structure is 12% less than that of the MLSCR with the traditional uniform base doping without adding extra process masks and increasing the chip area. Highlights: A new SCR with the variation lateral base doping structure is proposed. The variation lateral base doping structure can improve the turn-on speed of the SCR. The lateral base doping profile becomes steeper, and the turn-on time of the SCRs becomes smaller.